2021
DOI: 10.1093/jacamr/dlab049
|View full text |Cite
|
Sign up to set email alerts
|

WHO/INRUD core prescribing indicators and antibiotic utilization patterns among primary health care facilities in Ilala district, Tanzania

Abstract: Background Antibiotic use requires regular monitoring to prevent emergence of antibiotic resistance. Objectives To assess antibiotic prescribing patterns at health care facilities (HCF) in Ilala district, Tanzania. Methods A 1 year retrospective study was conducted in four HCFs using WHO/International Network of Rational Use of Drugs (INRUD) core prescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 11 publications
5
25
2
Order By: Relevance
“…Although most URTIs have a viral aetiology and have a selflimiting course, antibiotics are commonly prescribed. 32 This observation is in line with other previous pieces of published literature that have demonstrated this association. [33][34][35][36] The patient and the public should be informed that most of the acute URTIs are viral in origin and they require supportive therapy and not antibiotics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although most URTIs have a viral aetiology and have a selflimiting course, antibiotics are commonly prescribed. 32 This observation is in line with other previous pieces of published literature that have demonstrated this association. [33][34][35][36] The patient and the public should be informed that most of the acute URTIs are viral in origin and they require supportive therapy and not antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…However, when clinicians are unwilling to go through the procedures or when procedures are not available, prescription of an antibiotic will be the easy way out and without taking risk for possibility of untreated or delayed treatment of a bacterial infection. Although most URTIs have a viral aetiology and have a self-limiting course, antibiotics are commonly prescribed 32. This observation is in line with other previous pieces of published literature that have demonstrated this association 33–36.…”
Section: Discussionsupporting
confidence: 87%
“…Since URTIs were the most frequent diagnosis (22.8%), this may explain why the penicillins were the most prescribed antimicrobials (Table 2). Other studies have also shown that the penicillins (β-lactams) are among the most prescribed and dispensed class of antibiotics in ambulatory care given the high prevalence rates of URTIs [2,65,[74][75][76][77]. β-lactams have continued to be the mainstay of antimicrobial therapy due to their wide spectrum of activity against both gram positive and negative organisms.…”
Section: Discussionmentioning
confidence: 99%
“…All factors except with p-value <0.2 in univariate qualified for multivariate analysis as described elsewhere. 24 The p-value < 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%